US ARMY'S SAFETY AND SECURITY NEEDS REFLECTED IN KATHRYN BIGELOW'S THE HURT LOCKER (2009): A HUMANISTIC PSYCHOLOGICAL APPROACH - ASTUTI, ARINI INDRI (2011)
This study aims to explore the safety and security needs of major character on his personality. The objective of the research is to analyze the movie based on its structural elements and to analyze the major character based on psychological perspective. The researcher employs a qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is the movie itself. The secondary data sources are the books about humanistic psychology and the other sources such as internet. The method data collection is library research and the technique of data analyzing is descriptive technique. The result of this study shows that: firstly, the structural elements of the movie consist of character and characterization, casting, plot, point of view, mise en scene, sound, editing and cinematography. Secondly, the psychological analysis shows that safety and security needs are hard to get in Iraq.